2018
DOI: 10.1021/acs.est.8b03451
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Human Serum Albumin on Graphene Oxide: Implications for Protein Corona Formation and Conformation

Abstract: The influence of solution chemistry on the adsorption of human serum albumin (HSA) proteins on graphene oxide (GO) was investigated through batch adsorption experiments and the use of a quartz crystal microbalance with dissipation (QCM-D). The conformation of HSA layers on GO was also examined with the QCM-D. Our results show that an increase in ionic strength under neutral pH conditions resulted in stronger binding between HSA and GO, as well as more compact HSA layers on GO, emphasizing the key role of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 80 publications
0
28
1
Order By: Relevance
“…In this case, the water parameters such as ionic strength, solution pH, protein structure and concentration, had a pivotal influence on these nano–bio interactions [ 13 ]. Liu et al (2019) studied the protein corona formation of GO in aqueous medium containing divalent cations (i.e., Ca 2+ and Mg 2+ ), concluding that an increase in ionic strength under neutral pH conditions resulted in stronger binding between human serum albumin (HSA) and GO, as well as a more compact HSA protein layer (corona) on the GO, indicating an important role of electrostatic interactions in controlling HSA–GO complexes [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the water parameters such as ionic strength, solution pH, protein structure and concentration, had a pivotal influence on these nano–bio interactions [ 13 ]. Liu et al (2019) studied the protein corona formation of GO in aqueous medium containing divalent cations (i.e., Ca 2+ and Mg 2+ ), concluding that an increase in ionic strength under neutral pH conditions resulted in stronger binding between human serum albumin (HSA) and GO, as well as a more compact HSA protein layer (corona) on the GO, indicating an important role of electrostatic interactions in controlling HSA–GO complexes [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that BSA covalently bound to GO is a very interesting hybrid material for removal of uranium ions from seawater [ 7 ] and to produce filter membranes for metallic ion removal (i.e., AuCl 4 − , Co 2+ , Cu 2+ , Fe 2+ ) from aqueous solutions [ 8 ]. In addition, BSA has been considered as a model protein for assessing the fate of graphene oxide and other nanomaterials in the aquatic environment and colloidal nano-interactions with dissolved organic matter, such as humic substances [ 9 , 10 , 11 , 12 ]. Recently, Sun et al (2020) demonstrated that both protein structure and concentration are determinants for GO stability in aquatic environments, and that GO lateral size and solution chemistry are also crucial factors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to [30] the peak at ~1720 cm -1 should be attributed to C=O carboxyl and carbonyl groups, peak at 1640 cm -1 can be attributed to the skeletal vibrations of un-oxidized graphitic domains. Wide band at about ~ 1080 cm -1 appears due to hydroxyls [31].…”
Section: Nanosystemsmentioning
confidence: 99%
“…In addition to experimental findings 2937 , computational progress has also advanced our understanding of the protein corona, especially at the molecular level 3841 . In one demonstration, a multi-scale approach was developed to assess the role played by glucose and cholesterol during fibrinogen protein adsorption 38 .…”
Section: Introductionmentioning
confidence: 99%